Heparin‐free renal replacement therapy for chronic hemodialyzed patients at high risk for bleeding: a comparison of on‐line predilution hemodiafiltration with conventional hemodialysis. Issue 4 (10th May 2018) - Brunot, Vincent; Serre, Jean‐Emmanuel; Mourad, Georges; Klouche, Kada; Pernin, Vincent
Abstract: Background: In chronic hemodialysis patients with high risk of bleeding, optimal anticoagulation of the extracorporeal circuit is challenging. Heparin‐free hemodialysis (HD) with heparin‐coated AN69ST dialyzer is now considered as a good option and recommended by experts. Predilutional hemodiafiltration (HDF) may represent also a feasible alternative but has been poorly investigated. In this study, our aim was to evaluate the performance of on‐line automated predilution heparin‐free HDF as compared to conventional heparin‐free HD with a heparin‐coated membrane. Methods: We prospectively studied chronic hemodialysis patients at high risk of bleeding consecutively admitted to hospital who underwent heparin‐free renal replacement therapy (RRT) in our nephrology department. During 1 year, we routinely used heparin‐free HD and on‐line HDF in these settings. By using a propensity score, we compared HDF to HD regarding to session failure and efficiency. Results: One hundred and seventy‐nine patients were included in the study. Clotting phenomena necessitating premature termination of RRT sessions were encountered in 19% of them. After propensity score matching, the comparison of 77 HD and 77 HDF sessions showed no significant differences in duration of the sessions and in dialyzer clotting. By multivariate analysis, a blood flow less than 250 mL/min and recent surgery were the only parameters associated with extracorporeal circuit thrombosis. Conclusion: Heparin‐free on‐line predilutional HDF is a safe and effective technique for chronic hemodialysis patients with increased bleeding risk. The use of an automatic substitution volume that avoids filters hemoconcentration and of a blood flow above 250 mL/min strongly contribute to the observed performance. Further studies are, however, intended to confirm these results.